Strategi Guru Pendidikan Agama Islam Membentuk Karakter Religius di Madrasah Aliyah Al Barokah Purwantoro Wonogiri - Ana Wulan Lestari; Rido Kurnianto; Adib Khusnul Rois (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to examine the strategies used by Islamic Religi ous Education teachers in building the character of students at Madrasah Aliyah Al-Barokah Purwantoro. The presence of technology and its development has an impact on the character formation of students. This has become a particular concern for teachers, especially Islamic Religious Education teachers. A qualitative approach was used in this study using the case study method. Data were collected through triangulation, including direct observation within the madrasah environment; in-depth interviews with the principal, Islamic Religious Education teachers, and students of Madrasah Aliyah Al-Barokah Purwantoro; as well as document analysis. Based on the research findings, religious education plays a crucial role in  the character development of students at Madrasah Aliyah Al-Barokah Purwantoro. Therefore, the presence of Islamic Religious Education teachers is highly influential in building students’ character. The strategies employed by Islamic Religious Education teachers at Madrasah Aliyah Al-Barokah Purwantoro encompass three main aspects: classroom instructional strategies, exemplary behavior strategies, and habituation strategies. The implementation of this strategy has shown an increase in student discipline in terms of worship, although inconsistency in behavior outside the madrasah environment is still an issue. The success of this program is supported by the collaboration between the madrasah and parents, as well as the availability of worship facilities.